Mechanisms of carbon dioxide detection in the earthworm Dendrobaena veneta - Smith, Emily Jordan; Ryan, Jennifer L.; Lopresti, Sofia A.; Haghnazari, Dastan B. S.; Anderson, Karleigh A. S.; Lipson, Sarah J.; Johnson, Erik C.; Silver, Wayne L.; Saunders, Cecil J. (Frontiers in Ecology and Evolution, 2023)
Carbon dioxide (CO2) is a critical biological signal that is noxious to many animals at high concentrations. The earthworm Dendrobaena veneta lives in subterranean burrows containing high levels of CO2 and respires through its skin. Despite the ecological and agricultural importance of earthworms, relatively little is known about how they make decisions in their environment, including their response to elevated levels of CO2. To examine CO2 detection in this species, we designed the exudate assay, in which we placed an earthworm in a sealed container, exposed it to varying concentrations of CO2 for one minute, and recorded the amount of exudate secreted. Because earthworms excrete exudate in response to noxious stimuli, we hypothesized that the amount of exudate produced was proportional to the amount of irritation. We repeated these experiments after treatment with several blockers for molecules with potential involvement in CO2 detection, including carbonic anhydrases, guanylate cyclase, TRPA1, ASICs, and OTOP channels. We also confirmed the presence of homologous transcripts for each of these gene families in an epithelial transcriptome for D. veneta. Additionally, since organisms often detect CO2 levels indirectly by monitoring the conversion to carbonic acid (a weak acid), we used the exudate assay to evaluate aversion to additional weak acids (formic acid, acetic acid, and propionic acid). Earthworms excreted significantly more exudate in response to CO2 in a dosage-dependent manner, and this response was muted by the general carbonic anhydrase inhibitor acetazolamide, the carbonic anhydrase IX/XII inhibitor indisulam, the calcium channel blocker ruthenium red, the sodium channel blocker amiloride, and the acid-sensing ion channel blocker diminazene aceturate. These data provide evidence of the role of carbonic anhydrase and epithelial sodium channels in earthworm CO2 detection, establish that, similar to other subterranean-dwelling animals, earthworms are extremely tolerant of CO2, and contribute to our understanding of the mechanisms used by earthworms to detect and react to weak acids in their environment.